Stimulation of Children's Fine Motoric Abilities Age 4-5 Years Through Tracing Activities - Lilis Suryani; Raden Dewi R; Elminah; Nurlita Sari; RD Tati Hamidah; Kalipah (Universitas Panca Sakti Bekasi, 2023)
The purpose of this study is to provide an overview of early childhood stimulation so that it can be given for fine motor development in early childhood aged 4-5 years which is given through tracing activities. The research begins in July - December 2022 in the learning process in semester one, where the research is at Mutia 4 Cengkareng Islamic Kindergarten, West Jakarta. The research method used in this study is a qualitative approach with narrative methods. Stimulation for early childhood is very important for optimizing children's development, one of which is fine motor aspects. Activities carried out in the development of fine motor aspects are tracing activities. The results of this study obtained an illustration that tracing in Mutia 4 Cengkareng Islamic Kindergarten was done with joy, where the tracing process was carried out well by students of Mutia 4 Cengkareng Islamic Kindergarten, out of 26 children there were 20 students who were able to trace with very good development results (BSB), 3 students wanted to carry out tracing activities with the results developing according to expectations (BSH) and 3 students had problems participating in copying activities with results starting to appear (MM) due to factors not being interested in participating in tracing activities. This will also affect the readiness of the child in maximizing the movements of the wrists, fingers, and coordination of eye functions, so that in the next stage the child is able to coordinate movements of the wrists and fingers, as well as eye coordination movements properly and even sustainably until at the drawing and writing stage. Keywords: Stimulation, Fine Motoric, Tracing, Early Childhood